Dynamic emission rates of human activity in biological cleanrooms. (December 2022) - Zhang, Fan; Shiue, Angus; Fan, Yingying; Liu, Junjie; Meng, Han; Zhang, Jinxian; Leggett, Graham
Abstract: Humans are the primary source of particulate contamination in biological cleanrooms. Emitted particles can carry microorganisms, which severely reduces cleanliness. Due to the uncertainty of human particle emission rates, there is excessive ventilation in the cleanroom, resulting in waste of energy consumption. To resolve this problem, in this study a Class B area of a biopharmaceutical cleanroom was set up and used to run three different experiments. These experiments consisted of the dynamic process of a human entering the cleanroom, the effect of human activity on particle emissions, and the effect of air change rates on particle concentration. The particle concentration during human activities was measured, and the characteristics related to human activities were explored. Through these experiments, it was found that the particle concentration ≥0.5 μm was about 10–27 times larger than those ≥5 μm. The main influencing factors were determined, including activity intensity and cleanliness. According to the mass balance equation of the particles, it is quantitatively concluded that the equivalent value of the human particle emission rates is 50, 000–180, 000 particles/person/minute, and it is analyzed that the energy saving potential of the fan system in the biological cleanroom is more than 50%. Highlights: Experiments are carried out in a typical biological cleanroom. The spatial and temporal characteristics of human particle emissions are observed. Cleanliness and activity influence the human particle emission rates. Human particle emission equivalent is summarized for ventilation design. The energy saving of the fan system is above 50%.